H5N1 clade 2.3.2.1e lineage transition in Lao PDR during 2023–2024 associated with regional spread and human infection risk-associated receptor-binding features - Duc Duong Than; Boyoon Chang; Eun Lee; Watthana Theppangna; Seon-Ju Yeo; Hyun Park (Frontiers in Public Health, 2026)
Highly pathogenic avian influenza (HPAI) H5N1 viruses clade 2.3.2.1e has re-emerged in the Indochinese Peninsula, raising concerns about regional spread and zoonotic risk. We characterized eight H5N1 viruses isolated from 32 environmental and poultry-derived samples collected in Lao People’s Democratic Republic (Lao PDR) live bird markets during 2023–2024. Whole-genome and phylogenetic analyses showed that all isolates belonged to clade 2.3.2.1e and were distinct from the previously dominant Lao clade 2.3.2.1c, indicating lineage transition in poultry-associated viruses. The Lao isolates were distributed across regional sublineages rather than forming a single local cluster, suggesting repeated introductions and cross-border genetic connectivity. Segment-level nucleotide identities ranged from 97.2 to 99.9%, revealing a complex mosaic genotype constellation. All isolates retained the avian-associated glutamic acid residue at position 627 of polymerase basic protein 2 (PB2-627E) and the aspartic acid residue at position 701 of polymerase basic protein 2 (PB2-701D). Hemagglutinin (HA) analysis showed a conserved polybasic cleavage motif, PQRERRRKRGLF, and conserved HA1-123S, HA1-154N, HA1-263T, and HA2-497L, whereas isolate-level variation was observed at HA1-94, HA1-188, and HA1-223. Structural modeling and Molecular Mechanics-Generalized Born Surface Area (MM-GBSA) analysis of a representative isolate further highlighted receptor binding site (RBS) associated HA features. Importantly, RBS-associated HA variation was detected despite the absence of lysine residue at position 627 of polymerase basic protein 2 (PB2-627 K), suggesting that early molecular changes relevant to mammalian or human adaptation may arise before acquisition of canonical mammalian-adaptive polymerase mutations. These findings support sustained cross-border genomic surveillance and receptor-binding-focused characterization of H5N1 viruses circulating in Lao live bird markets.